Analisis Faktor – Faktor Yang Mempengaruhi Likuiditas Bank Di Indonesia - Eka Budiyati; Ratih Kusumawardhani (Jurnal Sosial Ekonomi Bisnis, 2022)
This study aims to determine the effect of bank size, Non Performing Loan (NPL) and Net Working Capital (NWC) on bank liquidity. The population of this study is the financial statements of banks listed on the Indonesia Stock Exchange. The sample of this study is the financial statements of banks listed on the Indonesia Stock Exchange which experienced losses in the 2016-2020 period. The research method used for the analysis of this research is the multiple linear regression method. The results of the discussion show that the variables of bank size, NPL and NWC together have an effect on bank liquidity. The results of the partial study with the t-test of the variable bank size had a positive and significant effect on bank liquidity with a significance value of 0.023. While the variables NPL and NWC have a negative and insignificant effect with a significance value of 0.124 and 0.249. Adjust R Square value of 0.177 indicates that the bank's liquidity can be 17.7% by the research variable while the rest is explained by other factors outside of this study.